The Effectivity of Bioactive Compounds from Montanoa hibiscifolia Benth Plants in inhibiting the Growth of Candida albicans. - Askar Fardiansyah; Khotibul Umam; Wawan Sujarwo; Putu Agus Hendra Wibawa (Jurnal Biologi Tropis, 2020)
Leucorrhoea is one of common disease in Indonesia that caused by infections of fungus Candida albicans. In dealing with this fungi, the synthetic and even an natural compound had used. Based on pre-screening data of the plants from botanical garden of Eka Karya Lipi Bali, there found apotential plant. This study aims to find the latest alternative treatment using the extract of Montanoa hiscifolia Benth plant from the collection of the "Eka Karya" LIPI Bali Botanical Garden which can inhibit fungal growth C. albicans. This research method begins with the literature skrining process using T.K Liem books and direct plant selection. After that proceed with the extraction process of 10 plant samples dose using the evaporator. The plant extracts were then tested directly on 4 types of fungi, from Eka Karya Lipi BaliÃ¢â¬â¢s collected.The dose used in ths study were 3%, 2%, 1% and 0.5% respectively. The final minimum dosage test was carried out using various concentrations of M. hiscifolia Benth plant extract which is the only type of best plant extract that can inhibit growth of C. albicans. Therefore, the minimum dosage test was carried out by reducing the concentration from 3 % to 0,0001 % to determine the minimum dose of extract M. hiscifolia Benth inhibiting the fungus C. albicans. This study found that at a concentration of 3 % was showed the best results for inhibition zone. On the contrary, at the concentration of 0,0001%, whereas the area of the inhibition zone was 7,2 mm andÃÂ  categorized as a medium inhibitor. At the last, we were compared the dose of commercial product that oftenly used asÃÂ  Leucorrhoea treatment with M. hibiscifolia benthÃ¢â¬â¢s bioactive and it proven the M. hibiscifolia benthÃÂ  havingÃÂ  a hight potential in order to cope the C. albicans. Further research might as well to check it bioactive compound that specifically play important role against the C. Albican. Beside, eventually develop this plant extract into a real product in order to be used as easy as for the people who need it.